Women’s Quest for Self-Identity and Emancipation in Manju Kapur’s Difficult Daughters - Mohammed Sharif Hangal (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Indian women novelists have represented women in varied social, emotional, and psychological roles; however, the postcolonial phase marks a decisive shift in the portrayal of female consciousness and resistance. Writers such as Kamala Markandaya, Nayantara Sahgal, Anita Desai, Shashi Deshpande, Bharati Mukherjee, Githa Hariharan, and Manju Kapur foreground women who challenge patriarchal authority and interrogate traditional gender roles. These writers depict women not merely as passive victims but as individuals striving for autonomy, self-identity, and emancipation within restrictive socio-cultural frameworks. Manju Kapur’s Difficult Daughters presents a nuanced portrayal of women’s struggles against social conventions, familial expectations, and moral constraints. This paper explores the psychological conflict, emotional turmoil, and existential anxiety of the protagonist Virmati in her quest for self-identity. Set against the backdrop of India’s freedom movement and the traumatic Partition of 1947, the novel draws a symbolic parallel between national liberation and a woman’s personal struggle for freedom. The study argues that Kapur presents emancipation as a complex, painful, and morally ambiguous process rather than a simplistic feminist triumph.